Research hotspots and trends on NF-κB in cognitive impairment: a bibliometric analysis - Bai, Lin; Xu, Fangyuan; Hu, Peijia; Shen, Zhiqiang; Xingxing, Su; Wang, Qingqing; Cheng, Hongliang (Frontiers in Medicine, 2024)
Background Cognitive impairment (CI) endangers the physical and mental health of patients in a significant manner, and it is expected that the number of people with CI in China will rise to 45.33 million by 2050. Therefore, CI has become a popular research topic. Inflammatory damage plays a key role in the pathogenesis of CI, and NF-κB is an important inflammatory signaling pathway. However, no bibliometric analysis regarding the relationship between CI and NF-κB has been reported. Methods A bibliometric analysis regarding NF-κB and CI from 1 January 2008 to 12 December 2023 was conducted in the Science Citation Index-Expanded of the Web of Science Core Collection. The frontiers, hotspots, and trends of research regarding the role of NF-κB in CI were identified. VOSviewer and CiteSpace were used to analyze the retrieved articles and identify the author, country, institution, and keywords, as well as co-cited authors, co-cited journals, and co-cited references. Results We analyzed 1,468 original articles and reviews. Publications on NF-κB in CI began in 2010 and increased sharply in 2018. Hong Hao was the most represented author, having published 19 articles, and Chinese authors published more studies than those from other countries. China Pharmaceutical University published the most papers; however, the United States has a strong influence and demonstrates international cooperation. The keywords “apolipoprotein e” and “therapeutic target” demonstrated strong citation bursts, and this tendency may persist in the upcoming years. Neuroinflammation demonstrated a strong influence in research regarding NF-κB in CI. Gut microbiota and ketogenic diet also play an important role in NF-κB in CI. Conclusion This bibliometric analysis and visualization using VOSviewer and CiteSpace revealed that the role of NF-κB in CI has become a research hotspot. The results of this study indicated that “neuroinflammation,” “microglial,” and “pathway” remain hotspots for future research. However, studies regarding NF-κB in CI have predominantly focussed on basic research; future research should include therapeutic targets, microbiota, and ketogenic diet.